2002
DOI: 10.1554/0014-3820(2002)056[1789:scaagr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Competitive Ability and Genetic Relatedness in Drosophila Melanogaster: Similarity Breeds Contempt

Abstract: Offspring of close relatives often suffer severe fitness consequences. Previous studies have demonstrated that females, when given a choice, will choose to avoid mating with closely related males. But where opportunities for mate choice are limited or kin recognition is absent, precopulatory mechanisms may not work. In this case, either sex could reduce the risks of inbreeding through mechanisms that occur during or after copulation. During mating, males or females could commit fewer gametes when mating with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 69 publications
7
44
3
Order By: Relevance
“…For example, early embryo mortality may reduce the reproductive success of genetically related partners (Birkhead et al 2004). Therefore, the strategies through which each sex influences inbreeding remain poorly understood (Mack et al 2002;Tregenza & Wedell 2002;Bretman et al 2004). Red junglefowl (Gallus gallus) live in small, sexually promiscuous populations where reproductive skew, limited dispersal of both sexes (Collias & Collias 1996) and male sexual coercion create a potential for inbreeding: around 4% of the copulations observed in freeranging, unconstrained groups of red junglefowl occurred between brothers and sisters, and also between mothers and sons (n ¼ 135; Collias & Collias 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, early embryo mortality may reduce the reproductive success of genetically related partners (Birkhead et al 2004). Therefore, the strategies through which each sex influences inbreeding remain poorly understood (Mack et al 2002;Tregenza & Wedell 2002;Bretman et al 2004). Red junglefowl (Gallus gallus) live in small, sexually promiscuous populations where reproductive skew, limited dispersal of both sexes (Collias & Collias 1996) and male sexual coercion create a potential for inbreeding: around 4% of the copulations observed in freeranging, unconstrained groups of red junglefowl occurred between brothers and sisters, and also between mothers and sons (n ¼ 135; Collias & Collias 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by the level of polyandry exhibited by this species, with females remating every3-5 days (Markow, 1996(Markow, , 2002. Finally, this suggests that there could be a conflict of interest between investing in environmentally similar mates while limiting the investment in related individuals (Mack et al, 2002). Preference for environmentally similar mates accounts for the recent findings that gut bacteria specificity can drive assortative mating, and potentially divergence between populations (reviewed in Brucker and Bordenstein, 2012), and this appears to be the case in D. melanogaster (Sharon et al, 2010(Sharon et al, , 2011.…”
Section: Discussionmentioning
confidence: 79%
“…Adults expressed a strong homogametic preference in mates presenting similarities in their odours, and gut bacteria were directly implicated in the recognition process. In D. melanogaster, various studies have attempted to test its ability to both recognise kin and avoid inbreeding (Spiess, 1987;Mack et al, 2002;Robinson et al, 2009Robinson et al, , 2012Tan et al, 2012), but controversies remain. It is clear that mating with related individuals leads to inbreeding costs, but uncertainty remains on the costs/benefits associated with mating with individuals of varying degrees of relatedness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that female multiple mating (polyandry) may have evolved as an inbreeding avoidance strategy mediated by post-copulatory mechanisms such as sperm-egg or sperm-female environment interactions [3][4][5], which could bias paternity towards unrelated or genetically compatible mates and hence reduce the costs of inbreeding. While growing evidence suggests that the genetic relatedness (or genetic similarity) between mating partners is associated with competitive fertilization success [6][7][8][9][10][11][12][13][14]although not always in the predicted direction (i.e. fertilization success biased in favour of males that are more genetically similar to the female [15][16][17][18])-most of these studies cannot exclude the influence of pre-copulatory mate choice or behavioural control of post-copulatory processes, which could bias fertilization success towards unrelated mates.…”
Section: Introductionmentioning
confidence: 99%